Exploring the role of Web 2.0 applications in the acquisition of digital literacy by first-year students at a South African University of Technology - Mhlongo, Mandlankosi Franscis (School of Education, 2025)
Despite the growing use of digital technologies in higher education, particularly in the university of technology (UoT) under investigation, many first-year students find it challenging to actively engage with online learning because of a lack of competence in digital literacy. This suggests that developing digital literacy is becoming more important for higher education students' success. This study adopted a skills-based approach, recognizing the core technical and information literacy practices and skills students need to effectively carry out their learning activities across their courses and beyond. The aim of this study was to explore the utilisation of Web 2.0 applications to facilitate the development of digital literacies among first-year Engineering students at a UoT. These applications include many different social media applications and websites, including blogs, discussion forums, wikis, social media networks and social bookmarking. A sequential mixed-methods strategy was adopted in this study to collect both pre-course (quantitative) and post-course (qualitative) data from a purposive sample of 275 first-year Engineering students. The pre-course questionnaire solicited data on students' lack of digital literacy to establish their digital literacy training needs. Over the course of two weeks, a digital literacy course was delivered with the goal of supporting students with navigating the transition between high school and university. After that, three focus groups were held with 27 students to explore the skills developed and their perceptions about the usage of Web 2.0 apps in facilitating their digital literacy acquisition. The pre- and post-course questions were developed using Ng's concepts and the three dimensions of digital literacy (technical, cognitive, and social-emotional). The intricate dimensions of student digital literacy were further analysed using Ng's framework. Additionally, the framework for digital literacy developed by Martin was used to explain how students' digital literacy developed as a result of their usage and competence with technology. Significant findings are that YouTube played a pivotal role in facilitating students' development of digital literacy. In comparison, discussion forums and blogs were not effective because students were uncomfortable posting or commenting in English, (the medium of instruction) and not their native language. Also, students felt that the duration of the digital literacy course was too short. The results of this study could inform attempts to enhance students' abilities to succeed in digital learning, including curriculum development, pedagogical approaches, and digital literacy programmes. It is recommended that: (i) the digital literacy course be extended over a longer period; and (ii) educators integrate digital literacy into the curriculum with the goal to support students from disadvantaged backgrounds who lack basic digital literacy.